2016
DOI: 10.1007/s00423-016-1455-7
|View full text |Cite
|
Sign up to set email alerts
|

Extralaryngeal branching of the recurrent laryngeal nerve: a meta-analysis of 28,387 nerves

Abstract: Introduction The recurrent laryngeal nerves (RLN) are branches of the vagus nerve that go on to innervate most of the intrinsic muscles of the larynx. Historically, the RLN has been considered to branch after it enters the larynx, but numerous studies have demonstrated that it often branches before. The wide variability of this extralaryngeal branching (ELB) has significant implications for the risk of iatrogenic injury. We aimed to assess the anatomical characteristics of ELB comprehensively. Methods Articles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
2
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 58 publications
0
49
2
9
Order By: Relevance
“…From Italy the only other study included in both SRs reported 31.1% (of 280 RLNs) as anterior to ITA (Sturniolo et al, 1999); two additional studies in SR2 involved only 94 and 12 total RLNs. Unweighted results for a specific RLN feature can vary greatly among studies from a single country (as shown by tabulations in Henry et al, 2016bHenry et al, , 2017.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From Italy the only other study included in both SRs reported 31.1% (of 280 RLNs) as anterior to ITA (Sturniolo et al, 1999); two additional studies in SR2 involved only 94 and 12 total RLNs. Unweighted results for a specific RLN feature can vary greatly among studies from a single country (as shown by tabulations in Henry et al, 2016bHenry et al, , 2017.…”
Section: Discussionmentioning
confidence: 99%
“…This study, however, actually did not meet SR1's criterion of having three categories. The 403 RLNs were classified only as either "superficial" (159) or "deep" (244) to ITA at their "first crossing;" 78 referred to "divided" RLNs among the 403 (Page et al, 2003) (i.e., extralaryngeal branching) (Henry et al, 2016b). The terms "superficial" and "deep" have been used elsewhere but not as the only categories for RLN-ITA relationships (Reed, 1943;Bergman et al, 2015).…”
Section: Both Sides Of the Body Combinedmentioning
confidence: 99%
“…Son yapılan ve 28 327 RLS'yi içeren metaanalizde intraoperatif çalışmalarda ortalama %39.2, kadavra çalışmalarında ise ortalama %73.3 oranında dallanma olduğu belirlenmiştir. [7] Ekstralaringeal dallanma aynı olguda tek taraflı ya da iki taraflı olabilir. [8,9] Zuckerkandl Tüberkülü (ZT): Ultimabrankial cisim (lateral tiroit cismi) ile median tiroit cisminin kaynaşma noktası olduğu kabul edilir ve genellikle posteriora doğru büyüyerek belirgin hale gelebilir.…”
Section: Reküren Laringeal Sinir Anatomik Seyriunclassified
“…), innervation of the same structure can differ between individuals (Matejcík, ; Henry et al. ; Wolf et al. ), the number of bones in the cranium can vary due to occasional appearance of wormian (intra‐sutural) bones (Hess, ; Ghosh et al.…”
Section: Introduction: the Paradox Of Anatomical Variationmentioning
confidence: 99%
“…One of the first things that medical students learn of human anatomy, usually to their frustration, is that its details are surprisingly variable. Blood vessels can vary in route and number (D aescu et al 2012;Bertrand et al 2014;Silva et al 2014;Marco-Clement et al 2016;Tomaszewski et al 2017), innervation of the same structure can differ between individuals (Matejc ık, 2010; Henry et al 2016;Wolf et al 2016), the number of bones in the cranium can vary due to occasional appearance of wormian (intrasutural) bones (Hess, 1946;Ghosh et al 2017), and there are many more examples of unpredictable anatomy in anatomical and surgical literature. Some of these differences may be specified genetically, but studies of monozygotic twins have demonstrated that histogenesis can vary even when driven by exactly the same 'genetic programme'.…”
mentioning
confidence: 99%